Social determinants of death among the elderly: a systematic literature review - Vanessa de Lima Silva; Eduarda Ângela Pessoa Cesse; Maria de Fátima Pessoa Militão de Albuquerque (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2014)
OBJECTIVE: This study aims at working on a systematic review of articles published on social determinants associated with the elderly mortality. METHODS: We searched articles published in Portuguese, English and Spanish language periodicals from January 1st 2007 to December 31st 2009, by means of Lilacs and Pubmed databases. Twenty cohort studies were identified, having most of them been developed in European, North-American and Asian countries. RESULTS: The articles analysed provided determinant social factors significantly associated with the elderly mortality: urban/rural and intercontinental variation, be part of ethnic minorities, financial stress, living conditions, schooling, social participation, gender and race discrimination, smoking, alcoholism, physical activities, instrumental activities of daily living, leisure, marital status, equality and healthy lifestyle. CONCLUSION: Mortality amongst the elderly is influenced by social determinants in many levels of reach, from determinants linked to lifestyle to socioeconomic macro-determinants. The actions on these determinants must be guided by the intersectorial perspective and regarded as a priority in the health sector, seeking to provide extended longevity with good quality of life for the population.